Computational Fluid Dynamics Modeling of Flow over Stepped Spillway - Raad Hoobi Irzooki; Jowhar Rasheed Mohammed; Afnan Salah Ameen (Tikrit Journal of Engineering Sciences, 2016)
In present paper, the computational fluid dynamics (CFD - program Flow-3D) was used to analyze and study the characteristics of flow energy dissipation over stepped spillways. Three different spillway heights ( ) (15, 20 and 25cm) were used. For each one of these models, three numbers of steps (N) (5, 10 and 25) and three spillway slopes (S) (0.5, 1 and 1.25) were used. Eight different discharges ranging (600-8500cm³/s) were passed over each one of these models, therefore the total runs of this study are 216. The energy dissipation over these models and the pressure distribution on the horizontal and vertical step faces over some models were studied. For verification purpose of the (CFD) program, the experimental work was conducted on four models of stepped spillway and five different discharges were passed over each model. The magnitude of dissipated energy on models was compared with results of numerical program under same conditions. The comparison showed good agreement between them with standard percentage error ranging between (-2.01 - 11.13%). Thus, the program Flow-3D is a reasonable numerical program which can be used in this study. Results showed that the energy dissipation increases with increased spillway height and decreased number of steps and spillway slope. Also, the energy dissipation decreases with increasing the flow rate. An empirical equation for measuring the energy dissipation was derived using the dimensional analysis. The coefficient of determination of this equation (R2 ) equals 0.766.